STUDI LITERATUR : PENGAJARAN PENGUKURAN (PANJANG, BERAT, DAN WAKTU) - Nurhaswinda; Eja Yolanda br. Pakpahan; Nurul Hasanah; Vinda Selfiana; Ziva Apriyanza (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the teaching of length, weight, and time measurement in elementary schools. The study employs a qualitative approach using a literature review method through descriptive analysis of 10 relevant scientific journals published between 2023 and 2025. The results of the study indicate that the teaching of length, weight, and time measurement in elementary schools requires an approach that is contextual, interactive, and based on real-world experiences to enhance students’ conceptual understanding. The use of concrete materials and varied learning strategies has proven effective in enhancing engagement, conceptual understanding, and problem-solving skills, as well as helping students connect measurement concepts to everyday life.